JP2013514963A - グラフェン分散液およびグラフェン−イオン性液体高分子複合物 - Google Patents
グラフェン分散液およびグラフェン−イオン性液体高分子複合物 Download PDFInfo
- Publication number
- JP2013514963A JP2013514963A JP2012545833A JP2012545833A JP2013514963A JP 2013514963 A JP2013514963 A JP 2013514963A JP 2012545833 A JP2012545833 A JP 2012545833A JP 2012545833 A JP2012545833 A JP 2012545833A JP 2013514963 A JP2013514963 A JP 2013514963A
- Authority
- JP
- Japan
- Prior art keywords
- graphene
- ionic liquid
- graphite
- dispersion
- liquid polymer
- Prior art date
- Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
- Pending
Links
Images
Classifications
-
- C—CHEMISTRY; METALLURGY
- C08—ORGANIC MACROMOLECULAR COMPOUNDS; THEIR PREPARATION OR CHEMICAL WORKING-UP; COMPOSITIONS BASED THEREON
- C08L—COMPOSITIONS OF MACROMOLECULAR COMPOUNDS
- C08L79/00—Compositions of macromolecular compounds obtained by reactions forming in the main chain of the macromolecule a linkage containing nitrogen with or without oxygen or carbon only, not provided for in groups C08L61/00 - C08L77/00
- C08L79/04—Polycondensates having nitrogen-containing heterocyclic rings in the main chain; Polyhydrazides; Polyamide acids or similar polyimide precursors
-
- C—CHEMISTRY; METALLURGY
- C08—ORGANIC MACROMOLECULAR COMPOUNDS; THEIR PREPARATION OR CHEMICAL WORKING-UP; COMPOSITIONS BASED THEREON
- C08K—Use of inorganic or non-macromolecular organic substances as compounding ingredients
- C08K3/00—Use of inorganic substances as compounding ingredients
- C08K3/02—Elements
- C08K3/04—Carbon
-
- B—PERFORMING OPERATIONS; TRANSPORTING
- B82—NANOTECHNOLOGY
- B82Y—SPECIFIC USES OR APPLICATIONS OF NANOSTRUCTURES; MEASUREMENT OR ANALYSIS OF NANOSTRUCTURES; MANUFACTURE OR TREATMENT OF NANOSTRUCTURES
- B82Y30/00—Nanotechnology for materials or surface science, e.g. nanocomposites
-
- B—PERFORMING OPERATIONS; TRANSPORTING
- B82—NANOTECHNOLOGY
- B82Y—SPECIFIC USES OR APPLICATIONS OF NANOSTRUCTURES; MEASUREMENT OR ANALYSIS OF NANOSTRUCTURES; MANUFACTURE OR TREATMENT OF NANOSTRUCTURES
- B82Y40/00—Manufacture or treatment of nanostructures
-
- C—CHEMISTRY; METALLURGY
- C01—INORGANIC CHEMISTRY
- C01B—NON-METALLIC ELEMENTS; COMPOUNDS THEREOF; METALLOIDS OR COMPOUNDS THEREOF NOT COVERED BY SUBCLASS C01C
- C01B32/00—Carbon; Compounds thereof
- C01B32/15—Nano-sized carbon materials
- C01B32/182—Graphene
- C01B32/194—After-treatment
-
- C—CHEMISTRY; METALLURGY
- C08—ORGANIC MACROMOLECULAR COMPOUNDS; THEIR PREPARATION OR CHEMICAL WORKING-UP; COMPOSITIONS BASED THEREON
- C08K—Use of inorganic or non-macromolecular organic substances as compounding ingredients
- C08K3/00—Use of inorganic substances as compounding ingredients
- C08K3/02—Elements
- C08K3/04—Carbon
- C08K3/041—Carbon nanotubes
-
- C—CHEMISTRY; METALLURGY
- C08—ORGANIC MACROMOLECULAR COMPOUNDS; THEIR PREPARATION OR CHEMICAL WORKING-UP; COMPOSITIONS BASED THEREON
- C08K—Use of inorganic or non-macromolecular organic substances as compounding ingredients
- C08K3/00—Use of inorganic substances as compounding ingredients
- C08K3/02—Elements
- C08K3/04—Carbon
- C08K3/045—Fullerenes
-
- H—ELECTRICITY
- H01—ELECTRIC ELEMENTS
- H01G—CAPACITORS; CAPACITORS, RECTIFIERS, DETECTORS, SWITCHING DEVICES, LIGHT-SENSITIVE OR TEMPERATURE-SENSITIVE DEVICES OF THE ELECTROLYTIC TYPE
- H01G9/00—Electrolytic capacitors, rectifiers, detectors, switching devices, light-sensitive or temperature-sensitive devices; Processes of their manufacture
- H01G9/004—Details
- H01G9/04—Electrodes or formation of dielectric layers thereon
- H01G9/042—Electrodes or formation of dielectric layers thereon characterised by the material
-
- H—ELECTRICITY
- H01—ELECTRIC ELEMENTS
- H01M—PROCESSES OR MEANS, e.g. BATTERIES, FOR THE DIRECT CONVERSION OF CHEMICAL ENERGY INTO ELECTRICAL ENERGY
- H01M4/00—Electrodes
- H01M4/02—Electrodes composed of, or comprising, active material
- H01M4/36—Selection of substances as active materials, active masses, active liquids
- H01M4/60—Selection of substances as active materials, active masses, active liquids of organic compounds
- H01M4/602—Polymers
-
- H—ELECTRICITY
- H01—ELECTRIC ELEMENTS
- H01M—PROCESSES OR MEANS, e.g. BATTERIES, FOR THE DIRECT CONVERSION OF CHEMICAL ENERGY INTO ELECTRICAL ENERGY
- H01M8/00—Fuel cells; Manufacture thereof
- H01M8/02—Details
-
- C—CHEMISTRY; METALLURGY
- C08—ORGANIC MACROMOLECULAR COMPOUNDS; THEIR PREPARATION OR CHEMICAL WORKING-UP; COMPOSITIONS BASED THEREON
- C08L—COMPOSITIONS OF MACROMOLECULAR COMPOUNDS
- C08L79/00—Compositions of macromolecular compounds obtained by reactions forming in the main chain of the macromolecule a linkage containing nitrogen with or without oxygen or carbon only, not provided for in groups C08L61/00 - C08L77/00
- C08L79/02—Polyamines
-
- Y—GENERAL TAGGING OF NEW TECHNOLOGICAL DEVELOPMENTS; GENERAL TAGGING OF CROSS-SECTIONAL TECHNOLOGIES SPANNING OVER SEVERAL SECTIONS OF THE IPC; TECHNICAL SUBJECTS COVERED BY FORMER USPC CROSS-REFERENCE ART COLLECTIONS [XRACs] AND DIGESTS
- Y02—TECHNOLOGIES OR APPLICATIONS FOR MITIGATION OR ADAPTATION AGAINST CLIMATE CHANGE
- Y02E—REDUCTION OF GREENHOUSE GAS [GHG] EMISSIONS, RELATED TO ENERGY GENERATION, TRANSMISSION OR DISTRIBUTION
- Y02E60/00—Enabling technologies; Technologies with a potential or indirect contribution to GHG emissions mitigation
- Y02E60/10—Energy storage using batteries
-
- Y—GENERAL TAGGING OF NEW TECHNOLOGICAL DEVELOPMENTS; GENERAL TAGGING OF CROSS-SECTIONAL TECHNOLOGIES SPANNING OVER SEVERAL SECTIONS OF THE IPC; TECHNICAL SUBJECTS COVERED BY FORMER USPC CROSS-REFERENCE ART COLLECTIONS [XRACs] AND DIGESTS
- Y02—TECHNOLOGIES OR APPLICATIONS FOR MITIGATION OR ADAPTATION AGAINST CLIMATE CHANGE
- Y02E—REDUCTION OF GREENHOUSE GAS [GHG] EMISSIONS, RELATED TO ENERGY GENERATION, TRANSMISSION OR DISTRIBUTION
- Y02E60/00—Enabling technologies; Technologies with a potential or indirect contribution to GHG emissions mitigation
- Y02E60/13—Energy storage using capacitors
-
- Y—GENERAL TAGGING OF NEW TECHNOLOGICAL DEVELOPMENTS; GENERAL TAGGING OF CROSS-SECTIONAL TECHNOLOGIES SPANNING OVER SEVERAL SECTIONS OF THE IPC; TECHNICAL SUBJECTS COVERED BY FORMER USPC CROSS-REFERENCE ART COLLECTIONS [XRACs] AND DIGESTS
- Y02—TECHNOLOGIES OR APPLICATIONS FOR MITIGATION OR ADAPTATION AGAINST CLIMATE CHANGE
- Y02E—REDUCTION OF GREENHOUSE GAS [GHG] EMISSIONS, RELATED TO ENERGY GENERATION, TRANSMISSION OR DISTRIBUTION
- Y02E60/00—Enabling technologies; Technologies with a potential or indirect contribution to GHG emissions mitigation
- Y02E60/30—Hydrogen technology
- Y02E60/50—Fuel cells
Landscapes
- Chemical & Material Sciences (AREA)
- Engineering & Computer Science (AREA)
- Nanotechnology (AREA)
- Organic Chemistry (AREA)
- Chemical Kinetics & Catalysis (AREA)
- Materials Engineering (AREA)
- Polymers & Plastics (AREA)
- Health & Medical Sciences (AREA)
- Medicinal Chemistry (AREA)
- Crystallography & Structural Chemistry (AREA)
- Condensed Matter Physics & Semiconductors (AREA)
- General Physics & Mathematics (AREA)
- Physics & Mathematics (AREA)
- Manufacturing & Machinery (AREA)
- Composite Materials (AREA)
- Inorganic Chemistry (AREA)
- Electrochemistry (AREA)
- Power Engineering (AREA)
- General Chemical & Material Sciences (AREA)
- Sustainable Energy (AREA)
- Sustainable Development (AREA)
- Life Sciences & Earth Sciences (AREA)
- Microelectronics & Electronic Packaging (AREA)
- Carbon And Carbon Compounds (AREA)
- Electric Double-Layer Capacitors Or The Like (AREA)
- Compositions Of Macromolecular Compounds (AREA)
- Battery Electrode And Active Subsutance (AREA)
- Inert Electrodes (AREA)
Abstract
【解決手段】本発明は、黒鉛をイオン性液体に入れて分散させることにより製造されたグラフェン分散液を用いてグラフェン-イオン性液体高分子複合物を製造することができる。
【選択図】図4
Description
0.03gを投入し、65℃の温度で6時間反応させることによりイオン性液体を重合した。この過程を経たグラフェン分散液はゲル状となり、ここにプロピレンカーボネート20gをさらに添加して撹拌すると、濃い灰色のグラフェン分散液が得られるが、この溶液が有機溶媒に均一に分散されているグラフェン分散液である。
25g、NaNO3 3.75g、H2SO4 170mlの溶液に撹拌して反応させることにより酸化黒鉛を製造し、前記酸化黒鉛は水で30分間撹拌し遠心分離することにより黄色の酸化グラフェン水分散液が得られる。前記酸化グラフェン水分散液19mlにイオン性液体高分子として、ポリ(1-ビニル-3-エチルイミダゾリウム)ブロマイド400mgを混合して撹拌することにより、イオン性液体高分子で安定化された酸化グラフェン水分散液を収得した。
Hummer方法(Hummers W,Offeman R., "Preparation
of graphite oxide", Jounal of the American Chemical
Society, 80, 1958, 1339)を用いて黒鉛(SP-1, Bay Carbon社製)を酸処理して酸化グラファイトを製造した。前記酸化グラファイトをプロピレンカーボネートを溶媒にして約1時間撹拌することによって、1.0mg/ml濃度の酸化グラフェンが分散された有機溶媒分散液を得る。
R., "Preparation of graphite oxide", Jounal of the American Chemical Society, 80, 1958, 1339)を用いて黒鉛(SP-1, Bay
Carbon社製)を酸処理して酸化グラファイトを製造した。酸化グラファイトを製造した後、プロピレンカーボネートを溶媒にしてこれを約1時間撹拌することによって、1.0mg/ml濃度の酸化グラフェンが分散された有機溶媒分散液を得る。
比較例2は、イオン性液体として1-ブチル-3-メチルイミダゾリウムビストリフルオロメチルスルホニルアミド[1-butyl-3-methylimidazoliumbis(trifluoromethyl)sulfonylamide]15mgを混合したことを除いては実施例5と同一である。比較例2の場合、還元反応時間が2時間である時、電気抵抗が約103Ohm/sqであるグラフェン-イオン性液体高分子複合物を製造することができたが、還元反応中にグラフェン-イオン性液体高分子複合物が溶液中で凝集する現象が発生した。
graphite)を高温熱処理したり、アルカリ金属を黒鉛の各層に挿入させた黒鉛(intercalated graphite)をマイクロ波で処理したり、若しくは黒鉛を電気化学的方法で処理することにより、黒鉛の各層間引力を減少させる。
of graphite oxide", Jounal of the American Chemical
Society, 80, 1958, 1339)を用いて黒鉛(SP-1、Bay Carbon社製)を酸処理して酸化グラファイトを製造し、これを水に入れ30分間撹拌することによって、1.0mg/ml濃度の酸化グラフェンが分散された水分散液を得る。
比較例3は、イオン性液体高分子を用いず、還元反応により収得したグラフェンにバインダー物質としてポリテトラフルオロエチレンを3wt%混合したことを除いては実施例12と同一である。
比較例4は、イオン性液体高分子を用いずグラフェンを製造することを除いては実施例13と同一である。
hexafluorophosphate]3gに入れて乳鉢でグラインドした後、再度30分間超音波分散してグラフェン-イオン性液体単量体を形成した。その後、前記溶液に重合開始剤として2,2-アゾビスイソブチロニトリル(AIBN)0.03gを投入し、65℃の温度で6時間反応させることにより、グラフェン-イオン性液体高分子複合物を形成した。
Claims (19)
- 黒鉛がイオン性液体に分散されているグラフェン分散液。
- 前記黒鉛は、一般黒鉛、酸化と還元処理された黒鉛、高温で熱処理された黒鉛、又はこれらを併用して処理された黒鉛であることを特徴とする請求項1に記載のグラフェン分散液。
- 前記分散は撹拌によりなされ、そして前記イオン性液体は陽イオンおよび陰イオンの組み合わせで構成された化合物であって、単量体(monomer)形態や高分子(polymer)形態であり、これらの成分のうちいずれか1つを用いるか、若しくは、2以上を混合して用いることを特徴とする請求項1又は請求項2に記載のグラフェン分散液。
- 前記イオン性液体は、陽イオンとして下記一般式(1)で表わすいずれかを用いるか、
(式中、R1〜R10は、互いに独立して次の群から選ばれるいずれか1つである。i)水素、ii)ハロゲン、iii)C1〜C25の炭化水素で構成されたアルキル、アルケニル、アルキニル、ベンジル、フェニルであって、O、N、SiおよびSを異種原子として含むことができ、又、選択的にCl、Br、F、I、OH、NH2、SHの群を含むことができる。)陰イオンとして、[CH3CO2]-、[HSO4]-、[CH3OSO3]-、[C2H5OSO3]-、[AlCl4]-、[CO3]2-、[HCO3]-、[NO2]-、[NO3]-、[SO4]2-、[PO4]3-、[HPO4]2-、[H2PO4]-、[HSO3]-、[CuCl2]-、Cl-、Br-、I-、[BF4]-、[PF6]-、[SbF6]-、[CF3SO3]-、[HCF2CF2SO3]-、[CF3HFCCF2SO3]-、[HCClFCF2SO3]-、[(CF3SO2)2N]-、[(CF3CF2SO2)2N]-、[(CF3SO2)3C]-、[CF3CO2]-、[CF3OCFHCF2SO3]-、[CF3CF2OCFHCF2SO3]-、[CF3CFHOCF2CF2SO3]-のうちいずれかを用いるか、あるいは、前記陽イオンと陰イオンとを含んだものを用いることを特徴とする請求項1〜3のうちいずれか1項に記載のグラフェン分散液。 - 前記イオン性液体高分子の分子量は1,000〜2,000,000g/molであるものを併用することを特徴とする請求項1〜4のうちいずれか1項に記載のグラフェン分散液。
- 前記分散液に重合開始剤を添加してイオン性液体を高分子量化することを特徴とする請求項1〜5のうちいずれか1項に記載のグラフェン分散液。
- 前記分散液におけるイオン性液体の陰イオン成分をイオン交換して溶媒系を変換することを特徴とする請求項1〜6のうちいずれか1項に記載のグラフェン分散液。
- 前記イオン性液体の陰イオン成分のイオン交換時にイオン交換反応を容易にするために、ゲル状のグラフェン分散液生成物にプロピレンカーボネート、1-メチルピロリドン、ジメチルホルムアミド、アセトニトリル、ニトロメタン、アセトン、テトラヒドロフラン溶媒をさらに添加することを特徴とする請求項1〜7のうちいずれか1項に記載のグラフェン分散液。
- 前記イオン性液体は、前記酸化グラフェンの重さに対して1倍以上添加されることを特徴とする請求項1〜8のうちいずれか1項に記載のグラフェン分散液。
- グラフェンにイオン性液体高分子が結合されたグラフェン-イオン性液体高分子複合物。
- 前記グラフェン-イオン性液体高分子複合物は、請求項1〜9のうちいずれか1項記載のグラフェン分散液での添加されるイオン性液体が単量体である場合、これを重合させるか、若しくは前記イオン性液体を高分子として用いて製造されることを特徴とする請求項10に記載のグラフェン-イオン性液体高分子複合物。
- 前記グラフェン5〜95重量%および前記イオン性液体高分子5〜95重量%で構成されることを特徴とする請求項10又は請求項11に記載のグラフェン-イオン性液体高分子複合物。
- イオン性液体を重合するための重合開始剤として、2,2-アゾビスイソブチロニトリル(AIBN)、1,1-アゾビスシクロヘキサンカルボニトリル(ABCN)、過酸化ベンゾイル(BP)のうちいずれか1つ以上を用いることを特徴とする請求項11又は請求項12に記載のグラフェン-イオン性液体高分子複合物。
- 前記重合開始剤は、前記イオン性液体100重量部に対して0.1〜3重量部を用いることを特徴とする請求項11〜13のうちいずれか1項に記載のグラフェン-イオン性液体高分子複合物の製造方法。
- 前記複合物は、バインダー、炭素材料、金属粒子および電気伝導性高分子を1つ以上さらに含むことを特徴とする請求項10〜14のうちいずれか1項に記載のグラフェン-イオン性液体高分子複合物。
- 前記バインダーは、ポリペルフルオロスルホン酸、ポリテトラフルオロエチレン、ポリビニリデンフルオライド共重合物のうちいずれか1つであり、
前記炭素材料は、活性炭素、黒鉛、カーボンブラック、カーボンナノチューブ、フラーレンのうちいずれか1つ以上であり、
前記電気伝導性高分子は、ポリアニリン、ポリピロール、ポリチオフェンおよびこれらの誘導体のうちいずれか1つ以上であることを特徴とする請求項15に記載のグラフェン-イオン性液体高分子複合物。 - 請求項1〜9に記載のグラフェン分散液の製造方法は、
前記黒鉛を酸化処理して酸化グラフェンを製造するステップと、
前記酸化グラフェンを溶媒に分散してイオン性液体を添加するか、若しくは前記酸化グラフェンに直接イオン性液体を添加してグラフェン分散液を作製するステップと、
前記分散液を100℃以上の温度で加熱したり還元剤を用いて還元させるステップと、
を含むことを特徴とするグラフェンの製造方法。 - 請求項1〜9に記載のグラフェン分散液の製造方法は、
膨張性黒鉛(expandable graphite)を高温熱処理したり、アルカリ金属を黒鉛の各層に挿入させた黒鉛(intercalated graphite)をマイクロ波で処理したり、若しくは黒鉛を電気化学的方法で処理した後、これをイオン性液体に入れて分散させることを特徴とするグラフェンの製造方法。 - 請求項17又は請求項18に記載のグラフェンの製造方法において、前記グラフェン分散液に添加されるイオン性液体が単量体である場合、これを重合させたり、あるいは前記イオン性液体を高分子として用いて製造されることを特徴とするグラフェン-イオン性液体高分子複合物の製造方法。
Applications Claiming Priority (7)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| KR20090129361 | 2009-12-22 | ||
| KR10-2009-0129361 | 2009-12-22 | ||
| KR20100014723 | 2010-02-18 | ||
| KR10-2010-0014723 | 2010-02-18 | ||
| KR10-2010-0061995 | 2010-06-29 | ||
| KR20100061995 | 2010-06-29 | ||
| PCT/KR2010/005401 WO2011078462A2 (ko) | 2009-12-22 | 2010-08-16 | 그래핀 분산액 및 그래핀-이온성 액체 고분자 복합물 |
Publications (1)
| Publication Number | Publication Date |
|---|---|
| JP2013514963A true JP2013514963A (ja) | 2013-05-02 |
Family
ID=44196227
Family Applications (2)
| Application Number | Title | Priority Date | Filing Date |
|---|---|---|---|
| JP2012545833A Pending JP2013514963A (ja) | 2009-12-22 | 2010-08-16 | グラフェン分散液およびグラフェン−イオン性液体高分子複合物 |
| JP2012545852A Pending JP2013534686A (ja) | 2009-12-22 | 2010-12-22 | 電気化学装置 |
Family Applications After (1)
| Application Number | Title | Priority Date | Filing Date |
|---|---|---|---|
| JP2012545852A Pending JP2013534686A (ja) | 2009-12-22 | 2010-12-22 | 電気化学装置 |
Country Status (6)
| Country | Link |
|---|---|
| US (2) | US20120261612A1 (ja) |
| EP (2) | EP2518103A4 (ja) |
| JP (2) | JP2013514963A (ja) |
| KR (2) | KR101550386B1 (ja) |
| CN (2) | CN102712779A (ja) |
| WO (2) | WO2011078462A2 (ja) |
Cited By (11)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| JP2013056815A (ja) * | 2011-09-08 | 2013-03-28 | Korea Inst Of Machinery & Materials | 還元された酸化グラフェン層及びコーティング層が順次に積層されたグラフェンペーパー及びその製造方法 |
| JP2015198089A (ja) * | 2014-03-31 | 2015-11-09 | 長興材料工業股▲ふん▼有限公司 | 電解質組成物 |
| KR20160010441A (ko) * | 2013-05-22 | 2016-01-27 | 베르살리스 에스.피.에이. | 그래핀을 함유하는 나노-구조 폴리머의 합성을 위한 양이온 중합 방법 |
| JP2016030713A (ja) * | 2014-07-29 | 2016-03-07 | 住友化学株式会社 | 成膜方法、膜及び分散液 |
| WO2016056582A1 (ja) * | 2014-10-10 | 2016-04-14 | 株式会社Adeka | 層状物質含有液及びその製造方法 |
| WO2016190225A1 (ja) * | 2015-05-28 | 2016-12-01 | 国立研究開発法人物質・材料研究機構 | 電極材料、その製造方法、および、それを用いた蓄電デバイス |
| WO2018117013A1 (ja) * | 2016-12-19 | 2018-06-28 | 株式会社Adeka | 層状物質含有液及びその製造方法 |
| JPWO2017141975A1 (ja) * | 2016-02-15 | 2018-12-06 | 国立大学法人東京工業大学 | sp2型炭素含有組成物、グラフェン量子ドット含有組成物およびこれらの製造方法、並びにグラファイトの剥離方法 |
| CN111602218A (zh) * | 2018-01-16 | 2020-08-28 | 株式会社村田制作所 | 蓄电器件以及蓄电器件的制造方法 |
| JP2022084534A (ja) * | 2020-11-26 | 2022-06-07 | 信越化学工業株式会社 | 生体電極組成物、生体電極、生体電極の製造方法、及び反応複合体 |
| JP2023106447A (ja) * | 2015-06-25 | 2023-08-01 | 株式会社半導体エネルギー研究所 | 二次電池用集電体 |
Families Citing this family (116)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| US20140150970A1 (en) | 2010-11-19 | 2014-06-05 | Ppg Industries Ohio, Inc. | Structural adhesive compositions |
| US8796361B2 (en) | 2010-11-19 | 2014-08-05 | Ppg Industries Ohio, Inc. | Adhesive compositions containing graphenic carbon particles |
| EP2658014A4 (en) * | 2010-12-22 | 2014-08-27 | Oceans King Lighting Science | ELECTRODE PLATE, PREPARATION METHOD THEREFOR, SUPERCAPSET AND LITHIUM ION BATTERY |
| WO2012118935A1 (en) | 2011-03-03 | 2012-09-07 | Proteotech Inc | Compounds for the treatment of neurodegenerative diseases |
| KR101275636B1 (ko) | 2011-08-30 | 2013-06-17 | 전자부품연구원 | 도핑 폴리머층을 포함하는 그래핀 기반 적층체 |
| PL222519B1 (pl) | 2011-09-19 | 2016-08-31 | Inst Tech Materiałów Elektronicznych | Sposób otrzymywania warstw grafenowych i pasta zawierająca nanopłatki grafenowe |
| ES2785095T3 (es) | 2011-12-21 | 2020-10-05 | Univ California | Red a base de carbono corrugada interconectada |
| KR101328495B1 (ko) | 2011-12-28 | 2013-11-13 | 전자부품연구원 | 음이온성 고분자가 표면처리된 세라믹 입자 및 표면처리방법 |
| WO2013123339A1 (en) | 2012-02-17 | 2013-08-22 | Aksay Ilhan A | Graphene-ionic liquid composites |
| AU2013230195B2 (en) | 2012-03-05 | 2017-04-20 | The Regents Of The University Of California | Capacitor with electrodes made of an interconnected corrugated carbon-based network |
| CN102683035B (zh) * | 2012-05-02 | 2014-09-24 | 清华大学 | 一种用于超级电容器的碳纳米电极材料及其制备方法 |
| US20130295290A1 (en) * | 2012-05-03 | 2013-11-07 | Ppg Industries Ohio, Inc. | Compositions with a sulfur-containing polymer and graphenic carbon particles |
| MX371065B (es) * | 2012-05-03 | 2020-01-14 | Ppg Ind Ohio Inc | Composiciones adhesivas que contienen partículas de carbono grafénicas. |
| KR101347198B1 (ko) * | 2012-05-03 | 2014-01-10 | 한국에너지기술연구원 | 염료감응태양전지 표면 코팅액의 제조방법, 그 코팅액 및 그를 도포한 염료감응태양전지 |
| RU2523425C2 (ru) * | 2012-05-12 | 2014-07-20 | Федеральное государственное бюджетное образовательное учреждение высшего профессионального образования "Челябинская государственная агроинженерная академия" | Суперконденсатор |
| US10030155B2 (en) | 2012-05-14 | 2018-07-24 | The University Of Tokyo | Graphene nanodispersion and method for preparing same |
| CN102732230A (zh) * | 2012-06-29 | 2012-10-17 | 华南理工大学 | 用于太阳能中高温热利用的离子液体纳米流体的制备方法 |
| CN103681000A (zh) * | 2012-09-25 | 2014-03-26 | 海洋王照明科技股份有限公司 | 一种石墨烯纸的制备方法 |
| CN103681002A (zh) * | 2012-09-26 | 2014-03-26 | 海洋王照明科技股份有限公司 | 掺氮石墨烯/离子液体复合电极及其制备方法与电容器 |
| CN103680977A (zh) * | 2012-09-26 | 2014-03-26 | 海洋王照明科技股份有限公司 | 石墨烯/离子液体复合电极及其制备方法与电容器 |
| DE102012109404A1 (de) * | 2012-10-02 | 2014-04-03 | Byk-Chemie Gmbh | Graphen-haltige Suspension, Verfahren zu deren Herstellung, Graphenplättchen und Verwendung |
| CN104718246B (zh) * | 2012-10-09 | 2017-03-08 | 沙特基础工业公司 | 基于石墨烯的复合材料、其制造方法及应用 |
| CN103779083A (zh) * | 2012-10-23 | 2014-05-07 | 海洋王照明科技股份有限公司 | 一种氮掺杂石墨烯/金属复合集流体及其制备方法 |
| US9545625B2 (en) * | 2012-11-09 | 2017-01-17 | Arizona Board Of Regents On Behalf Of Arizona State University | Ionic liquid functionalized reduced graphite oxide / TiO2 nanocomposite for conversion of CO2 to CH4 |
| KR20140075836A (ko) * | 2012-11-27 | 2014-06-20 | 삼성전기주식회사 | 전극 구조체 및 그 제조 방법, 그리고 상기 전극 구조체를 구비하는 에너지 저장 장치 |
| CN103839694B (zh) * | 2012-11-27 | 2016-09-07 | 海洋王照明科技股份有限公司 | 一种石墨烯/金属集流体的制备方法 |
| CN103839698A (zh) * | 2012-11-27 | 2014-06-04 | 海洋王照明科技股份有限公司 | 石墨烯复合电极材料及其制备方法和应用 |
| WO2014112337A1 (ja) * | 2013-01-15 | 2014-07-24 | 学校法人 芝浦工業大学 | 誘電材料及びこれを用いた電気化学素子 |
| CN103971951B (zh) * | 2013-01-28 | 2017-02-01 | 海洋王照明科技股份有限公司 | 超级电容器的制备方法 |
| CN103971944A (zh) * | 2013-01-28 | 2014-08-06 | 海洋王照明科技股份有限公司 | 石墨烯-离子液体复合材料及超级电容器的制备方法 |
| CN103971945A (zh) * | 2013-01-28 | 2014-08-06 | 海洋王照明科技股份有限公司 | 石墨烯-离子液体复合材料及超级电容器的制备方法 |
| CN103971943A (zh) * | 2013-01-28 | 2014-08-06 | 海洋王照明科技股份有限公司 | 石墨烯-离子液体复合材料及超级电容器的制备方法 |
| KR101455588B1 (ko) * | 2013-02-08 | 2014-10-31 | 신라대학교 산학협력단 | 적층 캐패시터 및 이를 이용한 전자파차폐막 |
| CN103991861A (zh) * | 2013-02-20 | 2014-08-20 | 海洋王照明科技股份有限公司 | 氮掺杂石墨烯及其制备方法 |
| CN104008894A (zh) * | 2013-02-21 | 2014-08-27 | 海洋王照明科技股份有限公司 | 掺氮石墨烯材料及其制备方法、掺氮石墨烯电极和电化学电容器 |
| KR101817260B1 (ko) | 2013-02-22 | 2018-01-11 | 삼성전자주식회사 | 그래핀-나노소재 복합체, 이를 채용한 전극 및 전기소자, 및 상기 그래핀-나노소재 복합체의 제조방법 |
| US9290524B2 (en) | 2013-03-15 | 2016-03-22 | Washington State University | Methods for producing functionalized graphenes |
| EP2970627A4 (en) * | 2013-03-15 | 2016-11-23 | Reliance Ind Ltd | POLYMER-GRAPH-NANO COMPOSITES |
| JP6028650B2 (ja) * | 2013-03-26 | 2016-11-16 | 東洋インキScホールディングス株式会社 | 炭素触媒、炭素触媒の製造方法、及び該炭素触媒を用いた触媒インキ並びに燃料電池 |
| KR102055776B1 (ko) * | 2013-03-28 | 2019-12-13 | 인텔렉추얼디스커버리 주식회사 | 질소 도핑한 환원된 산화 그래핀(N-doped rGO)을 이용한 n형 반도체의 제조 방법 |
| JP2014225508A (ja) | 2013-05-15 | 2014-12-04 | 住友電気工業株式会社 | 蓄電デバイス用電極、蓄電デバイスおよび蓄電デバイス用電極の製造方法 |
| CN103320056B (zh) * | 2013-07-11 | 2015-08-19 | 中国科学院宁波材料技术与工程研究所 | 集成材粘合剂 |
| ES2534575B1 (es) | 2013-09-24 | 2016-01-14 | Consejo Superior De Investigaciones Científicas (Csic) | Exfoliación de grafito con disolventes eutécticos profundos |
| KR20150063269A (ko) * | 2013-11-29 | 2015-06-09 | 삼성전자주식회사 | 리튬 공기 전지용 복합전극, 그 제조방법 및 이를 포함한 리튬 공기 전지 |
| KR101634961B1 (ko) | 2013-12-26 | 2016-07-01 | 한국과학기술원 | 그래핀 수화젤과 그래핀 수화젤 나노복합재료, 및 이들의 제조방법 |
| KR101614320B1 (ko) | 2013-12-31 | 2016-04-21 | 한국세라믹기술원 | 흑연산화물 농축 슬러리 코팅액 제조 방법 및 흑연산화물 코팅물 제조 방법 |
| WO2015131933A1 (en) | 2014-03-05 | 2015-09-11 | Westfälische Wilhelms-Universität Münster | Method of producing graphene by exfoliation of graphite |
| CN103887075B (zh) * | 2014-04-11 | 2017-04-26 | 电子科技大学 | 一种制造高比容量电极薄膜的方法 |
| KR101870544B1 (ko) * | 2014-04-28 | 2018-06-22 | 닝보 모시 테크놀로지 컴퍼니.,리미티드. | 그래핀 복합 분말체 소재 및 제조방법 |
| CN103980424A (zh) * | 2014-05-08 | 2014-08-13 | 嘉兴学院 | 一种石墨烯-聚离子液体复合材料及其制备方法和应用 |
| DE102014007137A1 (de) * | 2014-05-16 | 2015-11-19 | Dräger Safety AG & Co. KGaA | Elektrode für einen elektronischen Gassensor, Herstellungsverfahren für eine Elektrode und Verwendung einer Elektrode |
| KR102443607B1 (ko) | 2014-06-16 | 2022-09-16 | 더 리전트 오브 더 유니버시티 오브 캘리포니아 | 하이브리드 전기화학 전지 |
| CN104071778A (zh) * | 2014-06-20 | 2014-10-01 | 宁波墨西科技有限公司 | 石墨烯分散液及制备石墨烯材料粉体的方法 |
| CN104122311A (zh) * | 2014-07-29 | 2014-10-29 | 无锡百灵传感技术有限公司 | 一种基于富勒烯功能化改性电极的电化学传感器的制备方法 |
| WO2016063036A1 (en) * | 2014-10-21 | 2016-04-28 | 2-Dtech Limited | Methods for the production of 2-d materials |
| EP3016186A1 (en) | 2014-10-31 | 2016-05-04 | Max-Planck-Gesellschaft zur Förderung der Wissenschaften e.V. | Use of a poly(ionic liquid) as a binder material for electrodes in electrochemical devices |
| WO2016081638A1 (en) | 2014-11-18 | 2016-05-26 | The Regents Of The University Of California | Porous interconnected corrugated carbon-based network (iccn) composite |
| CN104525254B (zh) * | 2014-12-24 | 2016-08-17 | 东华大学 | 一种用于降解甲基橙的含金催化剂及其制备和应用 |
| CN104617291A (zh) * | 2015-01-24 | 2015-05-13 | 复旦大学 | 一种均匀碳包覆的锂离子电池正负极材料及其制备方法 |
| CN107429070B (zh) * | 2015-03-18 | 2021-06-22 | 株式会社Adeka | 层状物质含有液及其制造方法 |
| CN104843682A (zh) * | 2015-04-07 | 2015-08-19 | 大连理工大学 | 一种还原氧化石墨烯的制备方法及其应用 |
| KR102093118B1 (ko) | 2015-05-11 | 2020-05-27 | 한국과학기술원 | 그래핀 섬유 복합체, 이의 제조 방법 및 이를 포함하는 발열 소재 |
| KR101824207B1 (ko) * | 2015-06-19 | 2018-03-14 | 순천향대학교 산학협력단 | 탄소나노튜브 전계효과 트랜지스터의 제조방법 |
| WO2017083566A1 (en) * | 2015-11-12 | 2017-05-18 | Cornell University | High performance electrodes |
| KR101751733B1 (ko) | 2015-12-10 | 2017-06-28 | 성균관대학교산학협력단 | 음이온성 물질의 흡착 또는 센싱 방법 |
| US10377928B2 (en) | 2015-12-10 | 2019-08-13 | Ppg Industries Ohio, Inc. | Structural adhesive compositions |
| US10351661B2 (en) | 2015-12-10 | 2019-07-16 | Ppg Industries Ohio, Inc. | Method for producing an aminimide |
| US10655020B2 (en) | 2015-12-22 | 2020-05-19 | The Regents Of The University Of California | Cellular graphene films |
| CN105572200B (zh) * | 2016-01-06 | 2018-09-21 | 辽宁大学 | 一种在抗坏血酸存在的条件下检测多巴胺的修饰玻碳电极、制备方法及应用 |
| CN105548313A (zh) * | 2016-01-06 | 2016-05-04 | 辽宁大学 | 一种检测低浓度多巴胺的修饰电极及其制备方法和应用 |
| CN105462390B (zh) * | 2016-01-08 | 2017-08-25 | 石棉县亿欣钙业有限责任公司 | 环境友好型手持设备电子屏幕修复材料 |
| WO2017127539A1 (en) | 2016-01-22 | 2017-07-27 | The Regents Of The University Of California | High-voltage devices |
| CN105776187A (zh) * | 2016-01-27 | 2016-07-20 | 复旦大学 | 一种绿色环保制备高浓度超净石墨烯分散液的方法 |
| AU2017238201B2 (en) | 2016-03-23 | 2022-01-27 | Nanotech Energy, Inc. | Devices and methods for high voltage and solar applications |
| CN105633285A (zh) * | 2016-03-24 | 2016-06-01 | 浙江零维光伏科技有限公司 | 一种有机薄膜太阳能电池碳电极的制备方法 |
| KR102068257B1 (ko) * | 2016-03-31 | 2020-01-20 | 주식회사 엘지화학 | 고분자-그래핀 하이브리드의 제조 방법 |
| US10622163B2 (en) | 2016-04-01 | 2020-04-14 | The Regents Of The University Of California | Direct growth of polyaniline nanotubes on carbon cloth for flexible and high-performance supercapacitors |
| CN106053561B (zh) * | 2016-05-11 | 2018-08-17 | 华中科技大学 | 纳米石墨烯-碳纳米管-离子液体复合膜及其制备与应用 |
| KR101866190B1 (ko) * | 2016-05-31 | 2018-06-12 | 가천대학교 산학협력단 | 그래핀 금속나노입자-복합체 |
| CN106124255B (zh) * | 2016-06-17 | 2019-01-29 | 苍南县宝丰印业有限公司 | 一种石墨烯/离子液体复合材料富集空气中邻苯二甲酸酯的方法 |
| US11097951B2 (en) | 2016-06-24 | 2021-08-24 | The Regents Of The University Of California | Production of carbon-based oxide and reduced carbon-based oxide on a large scale |
| CN106430155A (zh) * | 2016-08-17 | 2017-02-22 | 吉林吉大地球科学与地质开发股份有限公司 | 一种基于离子液体制备石墨烯的方法 |
| JP7109790B2 (ja) | 2016-08-31 | 2022-08-01 | ザ リージェンツ オブ ザ ユニバーシティ オブ カリフォルニア | 炭素系材料を含むデバイス及びその製造 |
| CN106829941A (zh) * | 2017-04-07 | 2017-06-13 | 厦门大学 | 一种石墨烯的制备方法 |
| CN107189493A (zh) * | 2017-04-10 | 2017-09-22 | 桂林理工大学 | 一种离子液体改性石墨烯的制备方法 |
| KR101977232B1 (ko) * | 2017-05-29 | 2019-09-10 | 한국생산기술연구원 | 전극 및 이를 구비한 에너지 저장 복합 재료 |
| CN110892572B (zh) | 2017-07-14 | 2023-02-17 | 加利福尼亚大学董事会 | 用碳纳米点制备高导电多孔石墨烯用于超级电容器应用的简单方法 |
| KR102124789B1 (ko) * | 2017-07-21 | 2020-06-22 | 충남대학교산학협력단 | 스폰지 구조의 그래핀닷-백금니켈 하이브리드의 제조방법 및 그에 의해 제조된 그래핀닷-백금니켈 하이브리드 촉매 |
| CN107715283A (zh) * | 2017-09-14 | 2018-02-23 | 江门大诚医疗器械有限公司 | 石墨烯极性碎片溶液、石墨烯织物及阴道填塞器 |
| CN107574000A (zh) * | 2017-10-10 | 2018-01-12 | 广西科技大学 | 一种导电润滑脂的制备方法 |
| CN107596932B (zh) * | 2017-10-16 | 2020-11-17 | 黑龙江青谷酒庄有限公司 | 一种阳离子交换膜及其制备方法和应用 |
| DE102017223892A1 (de) * | 2017-12-29 | 2019-07-04 | Sixonia Tech Gmbh | Verfahren zur Herstellung eines funktionalisierten Halbleiter- oder Leitermaterials und dessen Verwendung |
| CN108461308B (zh) * | 2018-01-25 | 2019-11-12 | 齐鲁工业大学 | 一种石墨烯/聚离子液体复合材料及制备方法和应用 |
| CN108424613A (zh) * | 2018-02-02 | 2018-08-21 | 桂林理工大学 | 一种离子液体改性石墨烯/碳纳米管/环氧树脂复合材料的制备方法 |
| CN108530621B (zh) * | 2018-03-19 | 2021-01-01 | 厦门理工学院 | 一种可溶性的导电聚合物及其制备方法 |
| CN110734516B (zh) * | 2018-07-19 | 2022-03-01 | 中国石油天然气股份有限公司 | 一种离子液体改性氟化石墨烯制备含氟异丁烯、异戊二烯聚合物的方法 |
| CN111313067B (zh) * | 2018-12-11 | 2021-05-04 | 中国科学院大连化学物理研究所 | 基于离子液体有静电作用复合碱性电解质膜及制备和应用 |
| CN109576047B (zh) * | 2019-01-14 | 2021-06-15 | 西南交通大学 | 一种用离子液体制备高润滑性能石墨烯的方法 |
| CN109868340A (zh) * | 2019-02-20 | 2019-06-11 | 常州市宝平不锈钢制品有限公司 | 一种炼钢用高效增碳剂及其制备方法 |
| KR102817406B1 (ko) | 2019-02-27 | 2025-06-05 | 현대자동차주식회사 | 기계적 강성 및 수소 이온 전도성이 향상된 연료전지용 막-전극 접합체 및 그 제조방법 |
| CN110203917B (zh) * | 2019-05-29 | 2021-04-02 | 常熟理工学院 | 一种石墨烯超分散剂及其制备方法和在石墨烯中的应用 |
| US10938032B1 (en) | 2019-09-27 | 2021-03-02 | The Regents Of The University Of California | Composite graphene energy storage methods, devices, and systems |
| CN113387348B (zh) * | 2020-08-14 | 2022-07-19 | 中国科学院过程工程研究所 | 一种利用复合离子液体制备石墨烯的方法 |
| WO2022059368A1 (ja) * | 2020-09-17 | 2022-03-24 | 日東電工株式会社 | 分離膜、分離膜の製造方法及び分離膜を製造するための塗布液 |
| KR102415100B1 (ko) * | 2020-09-23 | 2022-06-30 | 주식회사 지에버 | 건·습식 그래핀 플레이크 조성물의 제조방법 및 이에 따라 제조된 그래핀 플레이크 조성물 |
| KR102415110B1 (ko) * | 2020-09-23 | 2022-07-01 | 주식회사 지에버 | 건·습식 그래핀 플레이크의 제조방법 및 이에 따라 제조된 그래핀 플레이크 |
| CN113248738B (zh) * | 2021-06-24 | 2022-07-01 | 西南科技大学 | 一种二维材料改性环氧树脂复合材料及其制备方法 |
| KR102681354B1 (ko) * | 2021-09-07 | 2024-07-03 | 포항공과대학교 산학협력단 | 층상 구조가 분리된 2차원 물질을 포함하는 나노시트 분산액의 제조 방법 |
| CN115015347B (zh) * | 2022-04-20 | 2024-03-26 | 华东师范大学 | 基于微管的离子液体胶体/水界面的搭建及其应用 |
| CN114852998A (zh) * | 2022-04-20 | 2022-08-05 | 西南交通大学 | 一种电化学插层法制备聚苯胺杂化石墨烯材料的方法 |
| CN115050984B (zh) * | 2022-06-15 | 2024-06-18 | 一汽解放汽车有限公司 | 一种改性氧化石墨烯涂层双极板的制备方法及其应用 |
| CN115368747B (zh) * | 2022-09-27 | 2023-04-07 | 西南交通大学 | 一种提升蜡质沥青低温性能的分散剂及其沥青和制备方法 |
| CN116009358A (zh) * | 2022-11-28 | 2023-04-25 | 北京师范大学 | 制备光刻胶-石墨烯导电复合体系的方法、由其获得的导电复合体系及其用途 |
| CN116515024B (zh) * | 2023-05-09 | 2025-04-11 | 辽宁大学 | 一种以Pickering乳液为模板的离子凝胶球的制备方法 |
| CN119170788B (zh) * | 2024-11-21 | 2025-03-11 | 碳一新能源(杭州)有限责任公司 | 聚合物改性石墨材料及其制备方法和应用 |
| CN119943985B (zh) * | 2025-04-07 | 2025-07-15 | 浙江华熔科技股份有限公司 | 一种具有多尺度导电网络且易于热塑成型的复合双极板 |
Citations (1)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| JP2008201604A (ja) * | 2007-02-17 | 2008-09-04 | Tokyo Institute Of Technology | カーボンオニオンおよびその製造方法、ならびに、ゲル組成物およびその製造方法 |
Family Cites Families (20)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| US7167353B2 (en) * | 2002-04-24 | 2007-01-23 | Nisshinbo Industries, Inc. | Ionic liquid, method of dehydration, electrical double layer capacitor, and secondary battery |
| US7321012B2 (en) * | 2003-02-28 | 2008-01-22 | The University Of Connecticut | Method of crosslinking intrinsically conductive polymers or intrinsically conductive polymer precursors and the articles obtained therefrom |
| JP2004289130A (ja) * | 2003-03-04 | 2004-10-14 | Jeol Ltd | 電気二重層キャパシタ |
| US20050227146A1 (en) * | 2003-12-12 | 2005-10-13 | Dania Ghantous | Medium rate and high rate batteries |
| WO2005064712A1 (en) * | 2003-12-30 | 2005-07-14 | Lg Chem, Ltd. | Ionic liquid-modified cathode and electrochemical device using the same |
| WO2006026064A2 (en) * | 2004-08-05 | 2006-03-09 | University Of Wyoming | Poly(ionic liquid)s as materials for co2 separation |
| CN101006535A (zh) * | 2004-08-30 | 2007-07-25 | 日清纺织株式会社 | 密闭型电容器 |
| KR20090019870A (ko) * | 2006-05-31 | 2009-02-25 | 막스-플랑크-게젤샤프트 츄어 푀르더룽 데어 비쎈샤프텐 에.파우. | 다공성의 전기 전도성 탄소 재료 및 그의 용도 |
| US7745047B2 (en) * | 2007-11-05 | 2010-06-29 | Nanotek Instruments, Inc. | Nano graphene platelet-base composite anode compositions for lithium ion batteries |
| JP5429845B2 (ja) * | 2007-12-04 | 2014-02-26 | Necエナジーデバイス株式会社 | 非水電解液、ゲル電解質及びそれらを用いた二次電池 |
| CN101910281A (zh) * | 2007-12-05 | 2010-12-08 | 纽约州立大学研究基金会 | 含有功能性离子液体和碳纳米填料的聚烯烃纳米复合材料 |
| KR101435999B1 (ko) * | 2007-12-07 | 2014-08-29 | 삼성전자주식회사 | 도펀트로 도핑된 산화그라펜의 환원물, 이를 포함하는 박막및 투명전극 |
| US9109113B2 (en) * | 2008-01-07 | 2015-08-18 | Wisys Technology Foundation | Method and apparatus for identifying and characterizing material solvents and composited matrices and methods of using same |
| CN100586848C (zh) * | 2008-01-22 | 2010-02-03 | 东北师范大学 | 带有离子液体阳离子基团修饰的具有导电性的单层石墨片的制备方法 |
| WO2009134707A2 (en) * | 2008-04-27 | 2009-11-05 | Board Of Regents, The University Of Texas System | Ultracapacitors and methods of making and using |
| TW201004869A (en) * | 2008-06-10 | 2010-02-01 | Nanotune Technologies Corp | Nanoporous materials and related methods |
| WO2010065346A1 (en) * | 2008-11-25 | 2010-06-10 | The University Of Alabama | Exfoliation of graphite using ionic liquids |
| CN101409368B (zh) * | 2008-12-05 | 2010-12-01 | 北京理工大学 | 一种采用离子液体型固态聚合物电解质的锂二次电池 |
| CN101575095B (zh) * | 2009-05-26 | 2012-12-12 | 北京大学 | 石墨烯的制备方法 |
| KR20110061909A (ko) * | 2009-12-02 | 2011-06-10 | 삼성전자주식회사 | 도펀트로 도핑된 그라펜 및 이를 이용한 소자 |
-
2010
- 2010-08-16 JP JP2012545833A patent/JP2013514963A/ja active Pending
- 2010-08-16 CN CN2010800592413A patent/CN102712779A/zh active Pending
- 2010-08-16 WO PCT/KR2010/005401 patent/WO2011078462A2/ko not_active Ceased
- 2010-08-16 US US13/518,421 patent/US20120261612A1/en not_active Abandoned
- 2010-08-16 EP EP10839659.9A patent/EP2518103A4/en not_active Withdrawn
- 2010-08-17 KR KR1020100079306A patent/KR101550386B1/ko not_active Expired - Fee Related
- 2010-12-22 US US13/518,432 patent/US20120256138A1/en not_active Abandoned
- 2010-12-22 JP JP2012545852A patent/JP2013534686A/ja active Pending
- 2010-12-22 CN CN2010800580204A patent/CN102763251A/zh active Pending
- 2010-12-22 WO PCT/KR2010/009235 patent/WO2011078585A2/ko not_active Ceased
- 2010-12-22 EP EP10839782A patent/EP2518805A2/en not_active Withdrawn
- 2010-12-22 KR KR1020127016365A patent/KR20120104264A/ko not_active Ceased
Patent Citations (1)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| JP2008201604A (ja) * | 2007-02-17 | 2008-09-04 | Tokyo Institute Of Technology | カーボンオニオンおよびその製造方法、ならびに、ゲル組成物およびその製造方法 |
Non-Patent Citations (3)
| Title |
|---|
| JPN6014037288; ZHOU,X. et al: '"Dispersion of graphene sheets in ionic liquid [bmim][PF6] stabilized by an ionic liquid polymer"' Chemical Communications Vol.46, No.3, 20091201, p.386-388 * |
| JPN6014037289; FUKUSHIMA, T. et al: '"Ionic Liquids for Soft Functional Materials with Carbon Nanotubes"' Chemistry - A European Journal Vol.13, 20070522, p.5048-508 * |
| JPN6014037290; PARK,S. et al: '"Chemical methods for the production of graphenes"' Nature Nanotechnology Vol.4, 20090329, p.217-224 * |
Cited By (23)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| JP2013056815A (ja) * | 2011-09-08 | 2013-03-28 | Korea Inst Of Machinery & Materials | 還元された酸化グラフェン層及びコーティング層が順次に積層されたグラフェンペーパー及びその製造方法 |
| JP2016519201A (ja) * | 2013-05-22 | 2016-06-30 | ベルサリス、ソシエタ、ペル、アチオニVersalis S.P.A. | グラフェン含有ナノ構造ポリマーの合成のためのカチオン重合プロセス |
| KR20160010441A (ko) * | 2013-05-22 | 2016-01-27 | 베르살리스 에스.피.에이. | 그래핀을 함유하는 나노-구조 폴리머의 합성을 위한 양이온 중합 방법 |
| KR102152233B1 (ko) | 2013-05-22 | 2020-09-07 | 베르살리스 에스.피.에이. | 그래핀을 함유하는 나노-구조 폴리머의 합성을 위한 양이온 중합 방법 |
| JP2015198089A (ja) * | 2014-03-31 | 2015-11-09 | 長興材料工業股▲ふん▼有限公司 | 電解質組成物 |
| US9735449B2 (en) | 2014-03-31 | 2017-08-15 | Eternal Materials Co., Ltd. | Electrolyte composition |
| JP2016030713A (ja) * | 2014-07-29 | 2016-03-07 | 住友化学株式会社 | 成膜方法、膜及び分散液 |
| JP2016079044A (ja) * | 2014-10-10 | 2016-05-16 | 株式会社Adeka | 層状物質含有液及びその製造方法 |
| WO2016056582A1 (ja) * | 2014-10-10 | 2016-04-14 | 株式会社Adeka | 層状物質含有液及びその製造方法 |
| WO2016190225A1 (ja) * | 2015-05-28 | 2016-12-01 | 国立研究開発法人物質・材料研究機構 | 電極材料、その製造方法、および、それを用いた蓄電デバイス |
| JPWO2016190225A1 (ja) * | 2015-05-28 | 2018-02-01 | 国立研究開発法人物質・材料研究機構 | 電極材料、その製造方法、および、それを用いた蓄電デバイス |
| JP7580524B2 (ja) | 2015-06-25 | 2024-11-11 | 株式会社半導体エネルギー研究所 | 二次電池用集電体 |
| US12080893B2 (en) | 2015-06-25 | 2024-09-03 | Semiconductor Energy Laboratory Co., Ltd. | Conductor, power storage device, electronic device, and method for forming conductor |
| JP2023106447A (ja) * | 2015-06-25 | 2023-08-01 | 株式会社半導体エネルギー研究所 | 二次電池用集電体 |
| US10961125B2 (en) | 2016-02-15 | 2021-03-30 | Tokyo Institute Of Technology | SP2 carbon-containing composition, graphene quantum dot-containing composition, methods of manufacturing thereof, and method of peeling graphite |
| JPWO2017141975A1 (ja) * | 2016-02-15 | 2018-12-06 | 国立大学法人東京工業大学 | sp2型炭素含有組成物、グラフェン量子ドット含有組成物およびこれらの製造方法、並びにグラファイトの剥離方法 |
| JP7076680B2 (ja) | 2016-12-19 | 2022-05-30 | 株式会社Adeka | 層状物質含有液及びその製造方法 |
| US11634545B2 (en) | 2016-12-19 | 2023-04-25 | Adeka Corporation | Layered-substance-containing solution and method of manufacturing same |
| JPWO2018117013A1 (ja) * | 2016-12-19 | 2019-10-24 | 株式会社Adeka | 層状物質含有液及びその製造方法 |
| WO2018117013A1 (ja) * | 2016-12-19 | 2018-06-28 | 株式会社Adeka | 層状物質含有液及びその製造方法 |
| CN111602218A (zh) * | 2018-01-16 | 2020-08-28 | 株式会社村田制作所 | 蓄电器件以及蓄电器件的制造方法 |
| JP2022084534A (ja) * | 2020-11-26 | 2022-06-07 | 信越化学工業株式会社 | 生体電極組成物、生体電極、生体電極の製造方法、及び反応複合体 |
| JP7507737B2 (ja) | 2020-11-26 | 2024-06-28 | 信越化学工業株式会社 | 生体電極組成物、生体電極、生体電極の製造方法、及び反応複合体 |
Also Published As
| Publication number | Publication date |
|---|---|
| US20120261612A1 (en) | 2012-10-18 |
| WO2011078585A3 (ko) | 2011-11-17 |
| EP2518805A2 (en) | 2012-10-31 |
| WO2011078462A3 (ko) | 2011-08-25 |
| US20120256138A1 (en) | 2012-10-11 |
| WO2011078585A2 (ko) | 2011-06-30 |
| CN102712779A (zh) | 2012-10-03 |
| CN102763251A (zh) | 2012-10-31 |
| EP2518103A4 (en) | 2014-07-30 |
| WO2011078462A2 (ko) | 2011-06-30 |
| KR20110073222A (ko) | 2011-06-29 |
| EP2518103A2 (en) | 2012-10-31 |
| JP2013534686A (ja) | 2013-09-05 |
| KR101550386B1 (ko) | 2015-09-08 |
| KR20120104264A (ko) | 2012-09-20 |
Similar Documents
| Publication | Publication Date | Title |
|---|---|---|
| KR101550386B1 (ko) | 그래핀 분산액 및 그래핀-이온성 액체 고분자 복합물 | |
| Song et al. | Room-temperature assembled MXene-based aerogels for high mass-loading sodium-ion storage | |
| Liu et al. | Conductive carbon nanofiber interpenetrated graphene architecture for ultra-stable sodium ion battery | |
| Wang et al. | High-performance flexible solid-state carbon cloth supercapacitors based on highly processible N-graphene doped polyacrylic acid/polyaniline composites | |
| Li et al. | Chemical intercalation of layered materials: from structure tailoring to applications | |
| Bandyopadhyay et al. | Facile synthesis of novel sulfonated polyaniline functionalized graphene using m-aminobenzene sulfonic acid for asymmetric supercapacitor application | |
| Qin et al. | A porous C/LiFePO4/multiwalled carbon nanotubes cathode material for Lithium ion batteries | |
| Chen et al. | Well-defined graphene/polyaniline flake composites for high performance supercapacitors | |
| Kwon et al. | Fabrication of graphene sheets intercalated with manganese oxide/carbon nanofibers: toward high‐capacity energy storage | |
| Giri et al. | In situ synthesis of cobalt doped polyaniline modified graphene composites for high performance supercapacitor electrode materials | |
| Xiao et al. | A simple process to prepare nitrogen-modified few-layer graphene for a supercapacitor electrode | |
| CN105849821B (zh) | 导电材料组合物、使用该导电材料组合物用于形成锂可再充电池的电极的浆料组合物和锂可再充电池 | |
| CN104300133B (zh) | 一种碳纳米管包覆的钛酸锂材料及其制备方法 | |
| Lee et al. | Understanding the impact of the morphology, phase structure, and mass fraction of MnO2 within MnO2/reduced graphene oxide composites for supercapacitor applications | |
| Liu et al. | The structure characteristic and electrochemical performance of graphene/polyaniline composites | |
| Narayanan | Single step hydrothermal synthesis of carbon nanodot decorated V2O5 nanobelts as hybrid conducting material for supercapacitor application | |
| Gottam et al. | Composite electrode material of MoO3‐MC‐SiO2‐PANI: Aqueous supercapacitor cell with high energy density, 1 V and 250,000 CD cycles | |
| Tu et al. | Mesoporous carbon nanomaterials with tunable geometries and porous structures fabricated by a surface-induced assembly strategy | |
| Kim et al. | Multidimensional polyaniline/reduced graphene oxide/silica nanocomposite for efficient supercapacitor electrodes | |
| Diggikar et al. | Unusual morphologies of reduced graphene oxide and polyaniline nanofibers-reduced graphene oxide composites for high performance supercapacitor applications | |
| Rajesh et al. | Expeditious and eco-friendly hydrothermal polymerization of PEDOT nanoparticles for binder-free high performance supercapacitor electrodes | |
| Parveen et al. | Manganese dioxide coupled with hollow carbon nanofiber toward high-performance electrochemical supercapacitive electrode materials | |
| Georgakilas et al. | Polypyrrole/MWNT nanocomposites synthesized through interfacial polymerization | |
| Silva et al. | Microwave-assisted hydrothermal synthesis and electrochemical characterization of niobium pentoxide/carbon nanotubes composites | |
| Crisci et al. | Easy direct functionalization of 2D MoS2 applied in covalent hybrids with PANI as dual blend supercapacitive materials |
Legal Events
| Date | Code | Title | Description |
|---|---|---|---|
| A621 | Written request for application examination |
Free format text: JAPANESE INTERMEDIATE CODE: A621 Effective date: 20130809 |
|
| A521 | Request for written amendment filed |
Free format text: JAPANESE INTERMEDIATE CODE: A523 Effective date: 20130909 |
|
| A977 | Report on retrieval |
Free format text: JAPANESE INTERMEDIATE CODE: A971007 Effective date: 20140725 |
|
| A131 | Notification of reasons for refusal |
Free format text: JAPANESE INTERMEDIATE CODE: A131 Effective date: 20140901 |
|
| A02 | Decision of refusal |
Free format text: JAPANESE INTERMEDIATE CODE: A02 Effective date: 20150212 |
